Cytogenetic findings and maternal age in patients with Down syndrome in a pediatric referral hospital from Peru: Hallazgos citogenéticos y edad materna en pacientes con Síndrome Down en un hospital de referencia pediátrico en el Perú - Llimpe Mitma de Barrón, Yesica (2023)
Introduction: Down syndrome is a congenital disorder caused by a total or partial trisomy of chromosome 21 and is considered the most common genetic cause of congenital malformations and intellectual disability. The objective of this study was to describe the cytogenetic alterations of patients with Down syndrome and their relationship with maternal age. Methods: Cross-sectional, descriptive-analytical study. 436 patients with Down syndrome admitted to the Instituto Nacional de Salud del Niño during the 2017-2019 period were included. The variables analyzed were: cytogenetic diagnosis and maternal age. Results: It was found that 99,3% (n=433) of patients presented some type of cytogenetic alteration and three patients presented a normal karyotype. The age of the patients at the time of sampling was between 0,03 and 17 years, the male/female ratio was 1.2:1. The most frequent cytogenetic alteration was free trisomy 21 (94,7%), followed by Robertsonian translocation (n=16) and mosaicism (n=6). In the case of maternal age, a median of 37 years was found (range: 13-47). Conclusions: Free trisomy 21 is the most common cytogenetic condition in Down syndrome; however, the Robertsonian translocation and mosaicisms were more frequent in patients whose mothers were les than 35 years old, suggesting that there are other risk factors than advanced maternal age in this group. Keywords: Down syndrome, cytogenetic analysis, maternal age, pediatrics.